THE JUANINO HOSPITAL OF NUESTRA SEÑORA DE LOS DOLORES DE TEZCOCO: EPIDEMICS IN AN INDIGENOUS CITY(1737, 1784AND 1813) (Tzintzun, Revista de Estudios Históricos, 2024)
The present work studies and analyzes six books of the sick and two books of thesick of the Hospital Juanino de Nuestra Señora de los Desamparados of the cityof Tezcoco elaborated in theXVIII century; but it focuses its attention on threeimportant epidemics that struck the local population in 1737 (Matlazahuatl),1784 (Influenza) and 1813 (Typhus). These manuscripts have remained inhistoriographic oblivion and their analysis allows us to know the ages, originand “sickness” that were treated in a hospital during the eighteenth century.
Keywords: Juaninos; hospitals; Tezcoco; epidemics; fevers